Modified functional ocular impression of post-enucleation socket: A case report - Arif, Fauzan; Ariyani, Ariyani; Tamin, Haslinda Z. (Indonesian Journal of Prosthodontic, 2021)
Introduction: The disfigurement associated with the loss of an eye can cause significant physical and psychological problems. Therefore, a good ocular prosthesis is needed to restore the patient's quality of life. One of the factors that determine the quality of an ocular prosthesis is accurately impression. In the case of enucleation where the eyes socket has a soft and movable tissue bad will result inaccurate impression. The difficulty of post enuclation impression in such case is the compression of the tissue eyes socket. This case report will discuss the modification in functional impression technique using a modified custom tray. Case: A 39-year-old male patient came to Dental Hospital Universitas Sumatera Utara with chief complaint an unaesthetic and loose left stock eye that had been used for 10 years. Clinical examination shows moderate depth eye socket with soft and movable tissue. Management: The functional impression technique was modified using a self-curing clear acrylic sclera without handle as a custom tray with 2 mm reduction on the intaglio surface and light body polyvinyl siloxane as impression material. Discussion: The aim of this modification is to avoid the tendency of the eye socket to compress during impression taking and to achieve a natural contour of the eyelid convexity because of the absence of the tray handle so the patient can close their eyes. Conclusion: This technique produces an ocular prosthesis that has a good retention with excellent aesthetic result.